LCN2 Is a Potential Biomarker for Radioresistance and Recurrence in Nasopharyngeal Carcinoma - Zhang, Meng-Xia; Wang, Li; Zeng, Lei; Tu, Zi-Wei (Frontiers in Oncology, 2021)
Background: Radioresistance-induced local failure, which can result in residual or recurrent tumors, remains one of the major causes of treatment failure in nasopharyngeal carcinoma (NPC). Lipocalin 2 (LCN2) is known to play important roles in cancer initiation, progression, and treatment responses. However, its role in the radioresistance of NPC remains unclear. Methods: Microarray data from the Gene Expression Omnibus (GEO) was screened for candidate biomarkers relating to the radioresistance of NPC. The expression of LCN2 in NPC cell lines was verified by quantitative real-time PCR (RT-qPCR) and western blotting. The effects of knockdown or overexpression of LCN2 on NPC radiosensitivity was examined using a soft agar colony formation assay and a γH2AX assay. LCN2 expression in NPC specimens was evaluated by immunohistochemistry. Survival outcomes were analyzed. A possible correlation between LCN2 and hypoxia-inducible factor 1-alpha (HIF-1A) was examined by western blotting and a tissue microarray. Results: LCN2 was highly expressed in the radioresistant NPC cell line CNE2R. Knocking down LCN2 enhanced the radiosensitivity of NPC cells by impairing their ability to repair DNA damage or proliferate, while ectopic expression of LCN2 conferred additional radioresistance to NPC cells. Immunohistochemical analysis of 100 NPC specimens revealed that LCN2 expression was significantly upregulated in radioresistant NPC tissues and was associated with NPC recurrence. Furthermore, a significant correlation between the expression of LCN2 and HIF-1A was detected. Conclusion: LCN2 is associated with radioresistance and recurrence in NPC, and may facilitate the development of a radioresistant phenotype through interacting with HIF-1A. Our data indicate that LCN2 is a promising target for predicting and overcoming radioresistance in NPC.